PENGARUH KEPUASAN KERJA DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA HOTEL ZAMRUD CIREBON - Dwi Budisatrio Novianto; Encu Sujana (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2015)
In the presence man resource in a firm holds momentous role. Respondent present business world creates Productivity job fires an employee that tall for firm development. Firm shall can build and increases work productivity in its environment. In increase its employee productivity corporate sails through some ways e.g. via compensation application that reasonably, application motivates, creating work condition that condusive, education, and training. This full age, progressively its tights emulation zoom carries on business to beget firm is brought up on daring for can keep viability. This research is done on Cirebon's Emerald Hotel. This research job satisfaction and ascendant Compensation to Productivity. To the effect this research is subject to be analyze influence Job and Compensation satisfaction for productivity to fire an employee. Sample that is utilized is Emerald Hotel employee Cirebon where foots up specified sample on this research as much 87 respondents by use of method sampling. The analyze who utilizing to cover validity quiz, reliabilitas's quiz, classic assuming quiz. The dates has already at o by use of program SPSS bases to test t one is done and result analisis can be known that job satisfaction (X1) having for positive and signifikan to Productivity as big as 2.634 and on Compensation result is known that positive ascendant and signifikan to Productivity as big as 2.794. Meanwhile bases result analisis can do Quiz f can be known that job satisfaction and Compensation has influence for Productivity to fire an employee with affecting point as big as 0,244 (R 2 ) or as big as 24,4 %. Key words : Job satisfaction, Compensation and Productivity